Scaffolding pada Konflik Kognitif dalam Pemecahan Masalah Matematika - Sutopo Sutopo (Ta'allum: Jurnal Pendidikan Islam, 2015)
Scaffolding is a help given for studentt in solving learning problem. It may be in the form of giving solution, example, and other action so that the student becomes autonomous. Scaffolding is useful help students to achieve higher competence in the cognitive conflict based teaching. In learning, cognitive conflict appears in various conditions such as naturally occurs when students are guessing, finding out that the hypothesis is wrong, and being provoked by the teachers and their classmates. Cognitive conflict is defined as conflict between cognitive structure and environment like experiment, demonstration, peer opinion, or a conflict between concept and cognitive structure.